(untitled) (Italiano LinguaDue, 2021)
Questo studio tratta l’espressione linguistica della futurità in italiano tramite i tempi verbali futuro semplice e presente. Un confronto con i rispettivi tempi verbali tedeschi sulla base di un ampio corpus contrastivo di attestazioni di lingua scritta e orale costituisce il fondamento per la formulazione di alcune proposte didattiche per discenti germanofoni di italiano lingua straniera. Futurity in Italian and German: theoretical-contrastive considerations and didactic perspectives This article deals with the linguistic expression of future events in Italian using the “future simple” and “present”. A contrastive Italian-German analysis, based on extensive written and oral corpora, constitutes the starting point for some didactic suggestions for German learners of Italian as a foreign language.